Is Subsidizing Entry An Optimal Policy? - Enrico Santarelle; Marco Vivarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
Public subsidies in support of new firm foundation are among the most frequently used instruments of industrial policy in the Euro zone. This paper analyses their effectiveness and efficiency vis-à-vis some features of the overall process of industry dynamics in Italian manufacturing. To this end, the survival and growth patterns of new small firms are investigated using a unique dataset on electrical and electronic engineering in Italy. As regards survival, our results confirm the findings of other studies, namely that the hazard rates are particularly high in the early stages of firm's life cycle. As far as growth is concerned, the study's main finding is that Gibrat's Law fails to hold in the years immediately following start-up, when smaller firms must 'rush' in order to achieve a size large enough to enhance their likelihood of survival; conversely, in later stages of firm's life cycle the Law cannot be rejected. These results radically question the use of subsidies as an optimal policy for the support of new entries, since the subsidy brings about a major bias in the process of market selection (including substitution and deadweight effects) and hampers the post-entry scale adjustment of newborn firms.
Keywords: 330